The marine food web of the Malpelo Fauna and Flora Sanctuary, Colombia: a structural analysis from a topological approach - Colombo Estupiñán-Montaño; Alberto Sánchez-González; Felipe Galván-Magaña; Fernando R. Elorriaga-Verplancken; Manuel J. Zetina-Rejón; Carlos J. Polo-Silva (Theoretical Ecology, 2026)

One-Click CT-Based Pipeline for Regional Quantification of Aortic Valve Fibrocalcific Degeneration - Marta Liberotti; Anna Palmisano; Alberto Colombo; Davide Vignale; Federica Piccione; Marco Bruno Ancona; Matteo Montorfano; Antonio Esposito (Annals of Biomedical Engineering, 2026)

Correction to: Ontogenetic feeding ecology of the silky shark (Carcharhinus falciformis) in the Colombian eastern tropical Pacific - Colombo Estupiñán‑Montaño; Daniel J. Villalobos‑Ramírez; Felipe Galván‑Magaña; Fernando R. Elorriaga‑Verplancken; Manuel J. Zetina-Rejón; Alberto Sánchez‑González; Carlos J. Polo‑Silva; Antonio Delgado‑Huertas (Environmental Biology of Fishes, 2025)

Ontogenetic feeding ecology of the silky shark (Carcharhinus falciformis) in the Colombian eastern tropical Pacific - Colombo Estupiñán-Montaño; Daniel J. Villalobos-Ramírez; Felipe Galván-Magaña; Fernando R. Elorriaga-Verplancken; Manuel J. Zetina-Rejón; Alberto Sánchez-González; Carlos J. Polo-Silva; Antonio Delgado-Huertas (Environmental Biology of Fishes, 2025)

3D Finite Element Analysis of Rock Deformation in Twin Circular Tunnels with a Transverse Gallery Using Plasticity and Time-Dependent Models - Felipe Pinto da Motta Quevedo; Carlos Alberto Magnus Maciel Colombo; Denise Bernaud; Samir Maghous (Geotechnical and Geological Engineering, 2025)

Characterization of artificial rainfall produced by a portable rainfall simulator using a rotating dynamic rainfall gauge system - Antônio Reynaldo de Sousa Costa; Lívia Alves Alvarenga; Michael Silveira Thebaldi; Luiz Antonio Lima; Alberto Colombo; Daniel Green; Jorge M. G. P. Isidoro (Hydrological Sciences Journal, 2024)

The VERA software: Implementation of the acute fish toxicity endpoint and its application to pharmaceutical compounds - Erika Colombo; Edoardo Luca Viganò; Giuseppa Raitano; Anna Lombardo; Alberto Manganaro; Alessio Sommovigo; Emilio Benfenati (Chemosphere, 2024)

Marine community trophic structure of Malpelo Island, Colombia from stable isotopes approach - Colombo Estupiñán-Montaño; Carlos J. Polo-Silva; Fernando R. Elorriaga-Verplancken; Alberto Sánchez-González; Manuel J. Zetina-Rejón; Antonio Delgado-Huertas; Jaiver Rojas-Cundumí; Felipe Galván-Magaña (Journal of Marine Systems, 2024)

Cardiorespiratory coupling in mechanically ventilated patients studied via synchrogram analysis - Davide Ottolina; Beatrice Cairo; Tommaso Fossali; Claudio Mazzucco; Antonio Castelli; Roberto Rech; Emanuele Catena; Alberto Porta; Riccardo Colombo (Medical & Biological Engineering & Computing, 2023)

Silver nano/microparticle toxicity in the shrimp Litopenaeus vannamei (Boone, 1931) - Sonia Astrid Muñoz Buitrago; Grecica Mariana Colombo; Juan Rafael Buitrago; Robson Matheus Marreiro Gomes; Alan Carvalho de Sousa; Virgínia Fonseca Pedrosa; Luís Alberto Romano; Leandro Machado de Carvalho; Franciele Rovasi Adolfo; Wilson Wasielesky Junior; Marcelo Estrella Josende; José Maria Monserrat (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Progress toward species-tailored prematuration approaches in carnivores - Alberto Maria Luciano; Federica Franciosi; Pritha Dey; Magdalena Ladron De Guevara; Noemi Monferini; Sai Kamal Nag Bonumallu; Giulia Musmeci; Fernanda Fagali Franchi; Rodrigo Garcia Barros; Martina Colombo; Valentina Lodde (Theriogenology, 2023)

Trophic connectivity between the terrestrial and marine ecosystems of Malpelo Island, Colombia, evaluated through stable isotope analysis - Colombo Estupiñán-Montaño; Manuel J. Zetina-Rejón; Felipe Galván-Magaña; Antonio Delgado-Huertas; Fernando R. Elorriaga-Verplancken; Carlos J. Polo-Silva; Javier Rojas-Cundumí; Daniel J. Villalobos-Ramírez; Alberto Sánchez-González (Marine Biology, 2023)

Sensitivity Analysis and Quantification of the Role of Governing Transport Mechanisms and Parameters in a Gas Flow Model for Low-Permeability Porous Media - Leonardo Sandoval; Monica Riva; Ivo Colombo; Alberto Guadagnini (Transport in Porous Media, 2022)
Recent models represent gas (methane) migration in low-permeability media as a weighted sum of various contributions, each associated with a given flow regime. These models typically embed numerous chemical/physical parameters that cannot be easily and unambiguously evaluated via experimental investigations. In this context, modern sensitivity analysis techniques enable us to diagnose the behavior of a given model through the quantification of the importance and role of model input uncertainties with respect to a target model output. Here, we rely on two global sensitivity analysis approaches and metrics (i.e., variance-based Sobol’ indices and moment-based AMA indices) to assess the behavior of a recent interpretive model that conceptualizes gas migration as the sum of a surface diffusion mechanism and two weighted bulk flow components. We quantitatively investigate the impact of (i) each uncertain model parameter and (ii) the type of their associated probability distribution on the evaluation of methane flow. We then derive the structure of an effective diffusion coefficient embedding all complex mechanisms of the model considered and allowing quantification of the relative contribution of each flow mechanism to the overall gas flow.

The hidden interplay between sex and COVID-19 mortality: the role of cardiovascular calcification - Alberto Cereda; Marco Toselli; Anna Palmisano; Davide Vignale; Riccardo Leone; Valeria Nicoletti; Chiara Gnasso; Antonio Mangieri; Arif Khokhar; Gianluca Campo; Alessandra Scoccia; Matteo Bertini; et al. (GeroScience, 2021)
Recent clinical and demographical studies on COVID-19 patients have demonstrated that men experience worse outcomes than women. However, in most cases, the data were not stratified according to gender, limiting the understanding of the real impact of gender on outcomes. This study aimed to evaluate the disaggregated in-hospital outcomes and explore the possible interactions between gender and cardiovascular calcifications. Data was derived from the sCORE-COVID-19 registry, an Italian multicentre registry that enrolled COVID-19 patients who had undergone a chest computer tomography scan on admission. A total of 1683 hospitalized patients (mean age 67±14 years) were included. Men had a higher prevalence of cardiovascular comorbidities, a higher pneumonia extension, more coronary calcifications (63% vs.50.9%, p<0.001), and a higher coronary calcium score (391±847 vs. 171±479 mm 3 , p <0.001). Men experienced a significantly higher mortality rate (24.4% vs. 17%, p =0.001), but the death event tended to occur earlier in women (15±7 vs. 8±7 days, p = 0.07). Non-survivors had a higher coronary, thoracic aorta, and aortic valve calcium score. Female sex, a known independent predictor of a favorable outcome in SARS-CoV2 infection, was not protective in women with a coronary calcification volume greater than 100 mm 3 . There were significant differences in cardiovascular comorbidities and vascular calcifications between men and women with SARS-CoV2 pneumonia. The differences in outcomes can be at least partially explained by the different cardiovascular profiles. However, women with poor outcomes had the same coronary calcific burden as men. The presumed favorable female sex bias in COVID-19 must therefore be reviewed in the context of comorbidities, especially cardiovascular ones.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

New insights into the trophic ecology of young white sharks (Carcharodon carcharias) in waters off the Baja California Peninsula, Mexico - Elena Tamburin; Fernando R. Elorriaga-Verplancken; Colombo Estupiñan-Montaño; Daniel J. Madigan; Alberto Sánchez-González; Mauricio Hoyos Padilla; Michelle Wcisel; Felipe Galván-Magaña (Marine Biology, 2020)

Dietary ontogeny of the blue shark, Prionace glauca, based on the analysis of δ13C and δ15N in vertebrae - Colombo Estupiñán-Montaño; Felipe Galván-Magaña; Alberto Sánchez-González; Fernando R. Elorriaga-Verplancken; Antonio Delgado-Huertas; Diego Páez-Rosas (Marine Biology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Irrigation distribution uniformity analysis on a lateral-move irrigation system - Lessandro Coll Faria; Bernardo Gomes Nörenberg; Alberto Colombo; Michael D. Dukes; Luis Carlos Timm; Samuel Beskow; Tamara Leitzke Caldeira (Irrigation Science, 2019)

Uncertainty quantification of overpressure buildup through inverse modeling of compaction processes in sedimentary basins - Ivo Colombo; Giovanni M. Porta; Paolo Ruffo; Alberto Guadagnini (Hydrogeology Journal, 2017)

Structural aspects of the fish assemblages in an exposed beach in south Brazil - Colombo Nathalia; Correia Alberto; Spach Henry (Frontiers in Marine Science, 2016)

Local and remote cellular responses following a surgical lesion in the Cebus apella cerebral cortex - Ximena A. Lanosa; Alberto Yáñez; Sabina Alzugaray; Jorge A. Colombo (Brain Structure and Function, 2012)

Production of tannase from wood-degrading fungus using as substrate plant residues: purification and characterization - R. M. Ordoñez; I. Colombo; M. R. Alberto; M. I. Isla (World Journal of Microbiology and Biotechnology, 2011)

The barley plastome mutant CL2 affects expression of nuclear and chloroplast housekeeping genes in a cell-age dependent manner - Noemí Colombo; Carola Emanuel; Verónica Lainez; Sara Maldonado; Alberto R. Prina; Thomas Börner (Molecular Genetics and Genomics, 2008)

Fungemia in cancer patients in Brazil: Predominance of non-albicans species - Marcio Nucci; Maria Isabel Silveira; Nelson Spector; Fernanda Silveira; Eduardo Velasco; Carlos Alberto Martins; Andrea Derossi; Arnaldo L. Colombo; Wolmar Pulcheri (Mycopathologia, 1998)